2020
DOI: 10.1515/pwp-2020-0048
|View full text |Cite
|
Sign up to set email alerts
|

Betriebliche Mitbestimmung in Deutschland: Verbreitung, Auswirkungen und Implikationen

Abstract: ZusammenfassungDie Mitbestimmung der Arbeitnehmer ist ein Eckpfeiler der betrieblichen Arbeitsbeziehungen in Deutschland. Claus Schnabel verdeutlicht, dass Betriebsräte und andere Vertretungsorgane weniger verbreitet sind als oft angenommen. Theoretische Ansätze postulieren sowohl positive als auch negative Auswirkungen von Mitbestimmung auf Betriebe und Arbeitnehmer. Ein Überblick über die empirische Forschungsliteratur zeigt einerseits, dass Mitarbeiterpartizipation langfristig die betriebliche Produktivität… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…Employees pursue those commitments on company time and receive full pay. They are tasked with representing employee interests at the top level role in German corporate organizations [106]. 18 Co-determination came under attack during the Nazi era, when these institutions were targeted, broken-up and replaced with authoritarian governance structures to stifle resistance and opposition [75].…”
Section: The Soft Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…Employees pursue those commitments on company time and receive full pay. They are tasked with representing employee interests at the top level role in German corporate organizations [106]. 18 Co-determination came under attack during the Nazi era, when these institutions were targeted, broken-up and replaced with authoritarian governance structures to stifle resistance and opposition [75].…”
Section: The Soft Tissuementioning
confidence: 99%
“…18 Today , "Betriebsräte" are in decline. Empirical research suggests that "Betriebsräte" have lost their appeal for employees as small company-sizes permit a direct negotiation with their management and that they are less likely to be established in owner-managed companies [106], which often is the case in start-ups. 19 The "Mittelstand", small and medium-sized companies that form an economic unit, is a phenomenon specific to German-speaking countries.…”
Section: Ai Ethics As "Verantwortung"mentioning
confidence: 99%
“…A large empirical literature has studied the firm-level effects of codetermination on worker outcomes, chiefly from the 1980s to early 2000s examining German codetermination (see Conchon [2011] for a summary of papers on German board-level representation and Addison [2009], Jirjahn and Smith [2018], and Schnabel [2020] for summaries of papers on German shop-floor representation). These studies compare the outcomes of workers in firms with versus without codetermination, or in industries subject to more stringent versus less stringent codetermination requirements, controlling for the influence of some confounding variables.…”
Section: Sources Of Evidencementioning
confidence: 99%
“…Keskinen (2017) and Harju et al (2021) found zero wage effects of Finnish shop-floor representation. Meanwhile, an older literature on German works councils produced mixed results (Addison 2009), and more recent studies found small positive effects on wages and moderate reductions in within-firm earnings inequalities (Jirjahn and Smith 2018;Hirsch and Mueller 2020;Schnabel 2020). The latter findings may reflect the particular strength of German works councils, which hold a variety of substantive co-decision-making rights and can also represent workers in firm-level wage negotiations, for example, if no sectoral bargaining agreement applies or if the agreement includes opening clauses ( §87 Betriebsverfassungsgesetz [Works Constitution Act]).…”
Section: Wages and Rent-sharingmentioning
confidence: 99%
“…The firm-specific economic consequences of works councils, also relating to wages, are surveyed by Addison (2009) and Schnabel (2020). Most importantly, the question of whether the remuneration of works councilors in Germany conforms to legal requirements has, to the best of our knowledge, not been examined based on representative data.…”
Section: Related Literaturementioning
confidence: 99%